A Comparative Double-blind Study to Evaluate the Efficacy of Coconut Water and Honey as Cytological Fixatives for Oral Smears - Bharadwaj Bordoloi; Aanchal Tandon; Arunima Goswami; Debojyoti Roy; Abhinav Srivastava; Apoorva Sharma (Contemporary Clinical Dentistry)
Introduction: Ninety-five percent ethanol is the routinely used and standard cytological fixative. However, commercially available ethanol is expensive and not freely available in some institutions. There is always a search for an ideal alternative. Aim and Objective: In the present study, we evaluated 100% coconut water (CW) and 30% aqueous honey solution as cytological fixative at different time points and compared them with routinely used spray fixative of ethanol. Materials and Methods: Oral smears were prepared from 30 healthy volunteers, and a total of 270 smears were prepared. From each volunteer, 9 smears were prepared. One smear was fixed in ethanol, four smears were fixed in 100% CW and four in 30% aqueous honey solution. Of the four smears fixed in CW or honey, one smear was fixed for 15 min, one for 30 min, one for 45 min, and one for 1 h, respectively. The slides were dried and then the smears were stained with Papanicolaou staining. Slides were evaluated by two independent observers who were blinded to the procedures. The following parameters were evaluated – nuclear staining, cytoplasmic staining, cell morphology, clarity of staining, and uniformity of staining. Statistical analysis was done using post hoc pairwise comparison, and P < 0.05 was considered to be statistically significant. Results: The results of the study showed that fixation with 30% aqueous solution of honey or 100% CW for more than 15 min yields useful and evaluable results. Conclusion: These readily available materials can be used as alternatives of alcohol in oral cytology.